2006
DOI: 10.1038/sj.emboj.7601252
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic growth in cardiac myocytes is mediated by Myc through a Cyclin D2-dependent pathway

Abstract: c‐Myc (Myc) is highly expressed in developing embryos where it regulates body size by controlling proliferation but not cell size. However, Myc is also induced in many postmitotic tissues, including adult myocardium, in response to stress where the predominant form of growth is an increase in cell size (hypertrophy) and not number. The function of Myc induction in this setting is unproven. Therefore, to explore Myc's role in hypertrophic growth, we created mice where Myc can be inducibly inactivated, specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
109
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 49 publications
13
109
0
2
Order By: Relevance
“…Myc is not expressed in the adult heart under normal physiological conditions; however, it is upregulated rapidly in response to virtually all forms of pathologic stress (17,18). Although work by our group and others has demonstrated that Myc is required for hypertrophic growth after hemodynamic stress (19)(20)(21), its role in regulating metabolism and mitochondrial biogenesis in the heart is unknown.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Myc is not expressed in the adult heart under normal physiological conditions; however, it is upregulated rapidly in response to virtually all forms of pathologic stress (17,18). Although work by our group and others has demonstrated that Myc is required for hypertrophic growth after hemodynamic stress (19)(20)(21), its role in regulating metabolism and mitochondrial biogenesis in the heart is unknown.…”
Section: Introductionmentioning
confidence: 86%
“…To evaluate whether Myc was required for the increased expression of genes involved in glucose metabolism typically seen after hypertrophic stimuli, we examined Myc-deficient mice in which Myc can be inducibly inactivated, specifically in adult myocardium with a tamoxifen-regulated Cre (21). Deletion of Myc attenuates hypertrophic growth in response to both hemodynamic and pharmacologic hypertrophic stimuli (21).…”
Section: Myc Is Upregulated In the Heart In Response To Multiple Pathmentioning
confidence: 99%
“…Studies in animal models have linked several master TFs (Gata4, c-Myc, Nfat3, NF-κB) to the induction of pathological gene sets that leads to the development of HF (14,(29)(30)(31). Moreover, physical exercise also highly influences cardiac function through increases in expression of these specific gene sets (32).…”
Section: Discussionmentioning
confidence: 99%
“…Directly relevant to our studies, both MYC and InR (INSR) signaling have been found to regulate muscle growth and maintenance in humans (Sandri et al, 2004;Southgate et al, 2007;Stitt et al, 2004;Zhong et al, 2006). Further, muscle atrophy is triggered by FOXO activation in several pathological conditions (Glass, 2003b;Sandri et al, 2004;Stitt et al, 2004).…”
Section: Research Articlementioning
confidence: 99%
“…Further, muscle atrophy is triggered by FOXO activation in several pathological conditions (Glass, 2003b;Sandri et al, 2004;Stitt et al, 2004). In addition, MYC function has been implicated in heart hypertrophy (Bello Roufai et al, 2007;Xiao et al, 2001;Zhong et al, 2006), a process that is conversely regulated by FOXO (Evans-Anderson et al, 2008;Skurk et al, 2005).…”
Section: Research Articlementioning
confidence: 99%